ENGLISH TEACHERS’ PEDAGOGICAL CONTENT KNOWLEDGE: THE DEGREE OF CONSISTENCY BETWEEN PERCEPTION AND IMPLEMENTATION - Ni Putu Diah Anggreni; Iga Lokita Purnamika Utami; Kadek Sintya Dewi (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2020)
This research aims to investigate teachers’ perceptions and their implementation of Pedagogical Content Knowledge (PCK) as well as compare teachers’ perceptions and implementation of PCK in teaching English for young learners. There are 3 primary school English teachers from 3 different public primary schools in Badung regency who were selected by using convenience sampling techniques. A mix-method design embedded with dominant qualitative is used in this study. In collecting the data, questionnaires, observation sheets, and interview guides were used.  The data were analyzed through descriptive qualitative. The results showed that the teachers had a strong positive perception of PCK meanwhile the teachers had a very weak level in implementing pedagogical content knowledge in the class. After both of the data were compared, it found that there was a lack of consistency between the teachers' perceptions and implementation of PCK in teaching English for young learners. According to the result, it clarified that there were some problems that encountered by the teachers during teaching young learners such as problem in using English in teaching, dealing with students' different characteristics and backgrounds, having problem in using media and having a different view about strategies used.